2016
DOI: 10.1080/21678707.2016.1215910
|View full text |Cite
|
Sign up to set email alerts
|

Translating HDAC inhibitors in Friedreich’s ataxia

Abstract: Introduction Friedreich's ataxia (FRDA) is an autosomal recessive neurodegenerative disease caused by expansion of a GAA·TTC triplet in the first intron of the FXN gene, encoding the essential mitochondrial protein frataxin. Repeat expansion results in transcriptional silencing through an epigenetic mechanism, resulting in significant decreases in frataxin protein in affected individuals. Since the FXN protein coding sequence is unchanged in FRDA, an attractive therapeutic approach for this disease would be to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 83 publications
0
28
0
Order By: Relevance
“…Friedreich's ataxia/FA (FXN) Lack of frataxin HDCA inhibitors (109/RG833, nicotinamide) to reverse epigenetic gene silencing Herman et al, 2006;Libri et al, 2014;Soragni and Gottesfeld, 2016 Ataxia telangiectasia/AT (ATM) Lack of ATM protein Glucocorticoid induction of non-canonic splicing events in mutant ATM mRNA precursor leading to novel ATM transcripts Menotta et al, 2017 Nucleic acids influencing specific gene expression drost et al, 2011;Lynch et al, 2010;Meier et al, 2012). While modulation of mitochondrial function and attenuation of oxidative load is logical and might provide some future therapeutic option, the use of iron chelators such as deferiprone should be tested with caution as recent evidence demonstrated that depletion of mitochondrial iron further exacerbate the phenotype (Martelli et al, 2015;Pandolfo et al, 2014).…”
Section: Modifiers Of Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Friedreich's ataxia/FA (FXN) Lack of frataxin HDCA inhibitors (109/RG833, nicotinamide) to reverse epigenetic gene silencing Herman et al, 2006;Libri et al, 2014;Soragni and Gottesfeld, 2016 Ataxia telangiectasia/AT (ATM) Lack of ATM protein Glucocorticoid induction of non-canonic splicing events in mutant ATM mRNA precursor leading to novel ATM transcripts Menotta et al, 2017 Nucleic acids influencing specific gene expression drost et al, 2011;Lynch et al, 2010;Meier et al, 2012). While modulation of mitochondrial function and attenuation of oxidative load is logical and might provide some future therapeutic option, the use of iron chelators such as deferiprone should be tested with caution as recent evidence demonstrated that depletion of mitochondrial iron further exacerbate the phenotype (Martelli et al, 2015;Pandolfo et al, 2014).…”
Section: Modifiers Of Gene Expressionmentioning
confidence: 99%
“…Histone deacetylase (HDAC) inhibitors reduce epigenetic silencing of genes by reverting chromatin to an open and active state for gene transcription. In preclinical studies, 2-aminobenzamide class I HDAC inhibitors were found to be the most effective to increase frataxin in patient-derived cell lines, including neuronal cells derived from patient iPSCs (induced pluripotent stem cells), and in GAA-based mouse models (Herman et al, 2006;Soragni and Gottesfeld, 2016). This led to the development of compound 109/RG833 for a phase Ib clinical trial in 20 adults with FA.…”
Section: Gene-related Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches tried to enhance frataxin transcription or translation. Interferon-γ (22), erythropoietin (23), or epigenetic modifiers such as histone deacetylase inhibitors (HDACis) (4,24) showed promising frataxin induction in in vitro and in vivo models, but the former 2 failed to reach endpoints in clinical trials (25,26) and the latter requires pharmacologic optimization to improve efficacy and reduce toxicity (27).…”
Section: Introductionmentioning
confidence: 99%
“…For example, common interventions for these patients are behavioural support and surgical procedures for the correction of orthopaedic or cardiac malformations. In this context, exploring known drugs effects in preclinical studies is the fundamental step for envisaging therapeutic avenues (Cobos et al, 2019;Soragni and Gottesfeld, 2016). Hence, the present work explored the effects of exogenous and endogenous molecules in RSTS experimental models, that should rescue the defective enzymatic activity underlying the condition.…”
Section: Discussionmentioning
confidence: 99%